Romance Languages and Linguistic Theory 1999 : Selected papers from 'Going Romance' 1999, Leiden, 9-11 December 1999. - D'hulst, Yves (John Benjamins Pub. Co., 2001)
This volume brings together a selection of articles presented at 'Going Romance' 1999. The articles focus on current syntactic and semantic issues in various Romance languages, including Catalan, French, Italian, Spanish, Portuguese, and a number of Northern Italian dialects. A large number of articles focus on negation, which was the theme of the workshop at Going Romance 1999, but other topics investigated include Wh- in situ, free relatives, exclamatives, lexical decomposition and thematic structure, unaccusative inversion, and temporal existential constructions. Most articles are comparati.